I'm so effing tired : a proven plan to beat burnout, boost your energy, and reclaim your life - Shah, Amy (Houghton Mifflin Harcourt, 2021)
"A guide to conquering burnout and increasing your energy from a leading medical doctor and nutrition expert"--